350–560 μm gelatin sponge particles combined with transcatheter arterial chemoembolization for the treatment of elderly hepatocellular carcinoma: The safety and efficacy. Issue 16 (April 2017) - Zhao, Guang Sheng; Li, Chuang; Liu, Ying; Ren, Zhi Zhong; Yuan, Xiao Lin; Zhou, Jun; Zhang, Yue Wei; Zhang, Ming
Abstract : Abstract: To retrospectively analyze the safety and efficacy of 350–560 μm gelatin sponge particles combined with single-chemotherapy drug transcatheter arterial chemoembolization (Gs-TACE) for the treatment of elderly hepatocellular carcinoma without surgical resection. Thirty elderly hepatocellular carcinoma patients without surgical resection, who received Gs-TACE in our hospital, were selected. Slowly injected gelatin sponge particles (350–560 μm)+ 10 mg lobaplatin injection into the regional embolization tumor target vessel. The Response Evaluation Criteria for Solid Tumors could be used to evaluate the tumor response after intervention surgery. Eighty-nine times of intervention TACE were conducted on the 30 patients. The average size of tumor was 8.3 cm. The median survival time was 28 months, and the 1 and 2-year survival rates were 89% and 58%, respectively. The Response Evaluation Criteria for Solid Tumors was used to evaluate the tumor response, and found that the complete response, partial response, and OR were 30%, 56.67%, and 86.67%, respectively, at 1 month after intervention surgery. The patients were divided into groups: 60 to 65 years age group (A), >65 to 75 years age group (B), and >75 years age group (C); the median survival times were 16, 32, and 33 months, respectively, and there was statistical difference between A group, B group, and C group. The analysis of prognosis factors showed that there was statistical significance in age, Barcelona Clinic Liver Cancer stage, portal vein invasion, and alpha fetal protein (AFP), and age was the protective factor. Gelatin sponge particles (350–560 μm), combined with transcatheter arterial chemoembolization, provide an alternative method for the treatment of elderly hepatocellular carcinoma without surgical resection.